Kinetics and Mechanism of Oxidation of Isoleucine by N-Bromophthalimide in Aqueous Perchloric Acid Medium - N. M. I. Alhaji; S. Sofiya Lawrence Mary (E-Journal of Chemistry)
The kinetics of oxidation of isoleucine with N-bromophthalimide has been studied in perchloric acid medium potentiometrically. The reaction is of first order each in [NBP] and [amino acid] and negative fractional order in [H+]. The rate is decreased by the addition of phthalimide. A decrease in the dielectric constant of the medium increases the rate. Addition of halide ions or acrylonitrile has no effect on the kinetics. Similarly, variation of ionic strength of the medium does not affect the reaction rate. The reaction rate has been determined at different temperatures and activation parameters have been calculated. A suitable mechanism involving hypobromous acid as reactive species has been proposed.